2022
DOI: 10.3390/cells11071067
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen Suppresses Lipid Deposition by Alleviating Insulin Resistance and Promoting Autophagy in Oleate-Induced L02 Cells

Abstract: Non-alcoholic fatty liver disease (NAFLD) held a high global prevalence in recent decades. Hepatic lipid deposition is the major characteristic of NAFLD. We aim to explore the mechanisms of psoralen on lipid deposition in NAFLD. The effects of psoralen on insulin resistance, lipid deposition, the expression and membrane translocation of glucose transporter type 4 (GLUT4), autophagy, and lipogenesis enzymes were determined on sodium oleate-induced L02 cells. Chloroquine and 3-MA were employed. The AMP-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Phosphorylation of AMPK, in particular the catalytic α subunit, has been shown to decrease lipid droplet formation and to alleviate hepatic steatosis in both diet-induced MAFLD models as well as in hepatocytes treated with FAs [80][81][82]. Previous studies have revealed that coumarin derivatives act as lipidlowering agents by activating AMPK-regulated lipogenic signaling pathways or AMPKmediated autophagy [83,84]. Esculetin decreases lipogenesis and lipid uptake in FA-treated hepatocytes by phosphorylating AMPKα at Thr172 and downregulating the expression of the target gene Acc [36,53].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of AMPK, in particular the catalytic α subunit, has been shown to decrease lipid droplet formation and to alleviate hepatic steatosis in both diet-induced MAFLD models as well as in hepatocytes treated with FAs [80][81][82]. Previous studies have revealed that coumarin derivatives act as lipidlowering agents by activating AMPK-regulated lipogenic signaling pathways or AMPKmediated autophagy [83,84]. Esculetin decreases lipogenesis and lipid uptake in FA-treated hepatocytes by phosphorylating AMPKα at Thr172 and downregulating the expression of the target gene Acc [36,53].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the multiple origins of FP where the soil condition, climate, and processing methods vary from one to another, major differences were witnessed in the quality of FP, 13 posing a challenge to fully monitor and accurately evaluate its overall quality. Active ingredients in FP are coumarins, flavonoids, and phenolic compounds including psoralen, 14 isopsoralen, 15 bakuchiol, 16 psoralidin, 17 bavachinin, 18 and so forth. Nevertheless, only the total amount of psoralen and isopsoralen were stipulated in the Chinese Pharmacopoeia (ChP) for the quality standard of FP, which inevitably contradicts the multi‐component and multi‐target characteristics of TCM.…”
Section: Introductionmentioning
confidence: 99%